A Study on Indian Journalists and their Stressful Working Conditions - Dr.Trishu Sharma, (International Journal of Research in Informative Science Application & Techniques (IJRISAT), 2022)
Journalism is considered as fourth pillar of any democratic society and it is only a Journalist who can take many challenges to bring truth in front of society. But sometimes journalist has to face difficult and stressful conditions while working in field where they have serious threat for their life even. In this paper researcher is trying to explore various challenging and stressful conditions of Indian Journalists along with the data which reveals that why India is considered a dangerous country for Journalists. Mostly Secondary data is taken to analyze various aspects of working Conditions of Journalist. Through this paper the actual dangerous conditions for Indian Journalist will be analyzed and explored.